2004
DOI: 10.1118/1.1781332
|View full text |Cite
|
Sign up to set email alerts
|

Radiation absorbed dose distribution in a patient treated with yttrium‐90 microspheres for hepatocellular carcinoma

Abstract: We have implemented a three-dimensional dose calculation technique accounting for dose inhomogeneity within the liver and tumor of a patient treated with 90Y microspheres. Single-photon emission computed tomography (SPECT) images were used to derive the activity distribution within liver. A Monte Carlo calculation was performed to create a voxel dose kernel for the 90Y source. The activity distribution was convolved with the voxel dose kernel to obtain the three-dimensional (3D) radiation absorbed dose distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 14 publications
1
61
1
1
Order By: Relevance
“…Point kernels can also be integrated over a cubic volume to provide dose voxel kernels similar to the voxel S factors. 42 Sarfaraz et al 43 present an image-based 3D dosimetry for 90 Y microspheres. The bremsstrahlung SPECT imaging does not have adequate resolution for dose distribution calculation.…”
Section: Ivc Image-based Dosimetrymentioning
confidence: 99%
“…Point kernels can also be integrated over a cubic volume to provide dose voxel kernels similar to the voxel S factors. 42 Sarfaraz et al 43 present an image-based 3D dosimetry for 90 Y microspheres. The bremsstrahlung SPECT imaging does not have adequate resolution for dose distribution calculation.…”
Section: Ivc Image-based Dosimetrymentioning
confidence: 99%
“…16 An optimal treatment planning should include 3D voxelbased dosimetry, accounting for nonuniform absorbed dose distributions when studying dose-effect correlations. 9,[17][18][19][20][21][22][23] Image-based 3D dosimetry can be performed in several ways: direct Monte Carlo (MC) simulation, which is considered the gold standard; 9,[24][25][26][27][28][29][30] convolution calculations by voxel S-values, reliable in nearly uniform density tissue; 19,[31][32][33][34][35][36] local energy deposition method. 18,20,[36][37][38][39] Activity distribution quantification by SPECT is the major concern, due to physical and clinical degrading factors of the images.…”
Section: Introductionmentioning
confidence: 99%
“…Despite positive results from published studies,6, 7 the reported doses assume that the activity distribution within the treatment volume is uniform. Quantitative patient‐specific 90 Y dosimetry has been studied using bremsstrahlung single photon emission computed tomography (SPECT)/computed tomography (CT) 8, 9, 10, 11 and positron emission tomography (PET)/CT 12, 13, 14, 15, 16. However, such dosimetric studies have utilized research software that is not readily available to the medical community and have not illustrated scenarios where voxel‐based dosimetry could be used to predict treatment response.…”
Section: Introductionmentioning
confidence: 99%